2012
DOI: 10.1016/s0027-9684(15)30126-7
|View full text |Cite
|
Sign up to set email alerts
|

The Association Among Specialty, Race, Ethnicity, and Practice Location Among California Physicians in Diverse Specialties

Abstract: Background Minority physicians are more likely than their counterparts to work in underserved communities and care for minority, poor, and uninsured patients, but much of this research has examined primary care physicians alone. Few have investigated whether non–primary care specialists of minority backgrounds are more likely to serve the underserved than nonminority specialists. Objective We examined whether underrepresented minority (URM) physicians from a wide variety of specialties are more likely than n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
94
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 12 publications
2
94
0
Order By: Relevance
“…1214,16,17,31,36,37,43,55,57,59 In a national study, Rabinowitz et al demonstrated that URM generalists were nearly three times more likely to practice in an underserved area when compared with non-URM physicians. 36 State-level studies indicated that black and Latino physicians were more likely to practice in a shortage area when compared with their non-URM colleagues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1214,16,17,31,36,37,43,55,57,59 In a national study, Rabinowitz et al demonstrated that URM generalists were nearly three times more likely to practice in an underserved area when compared with non-URM physicians. 36 State-level studies indicated that black and Latino physicians were more likely to practice in a shortage area when compared with their non-URM colleagues.…”
Section: Resultsmentioning
confidence: 99%
“…36 State-level studies indicated that black and Latino physicians were more likely to practice in a shortage area when compared with their non-URM colleagues. 13,43 …”
Section: Resultsmentioning
confidence: 99%
“…[22] It has been demonstrated that despite an overall physician shortage in AA and Hispanic communities, AA and Hispanic physicians are more likely to care for AA and Hispanic patients in medically underserved areas, provide more effective care due to lack of cultural or language barriers, and more likely to care for patients with Medicaid or no insurance. [23, 24] However, efforts to increase AA and Hispanic representation in medical and public health schools so that they reflect the general population have been thwarted by attacks on affirmative action programs. [25] These attacks have a direct, negative impact on the most economically and medically vulnerable populations who will continue to have poor outcomes unless institutional diversity is addressed in health policy, health delivery and medical education systems.…”
Section: - Discussionmentioning
confidence: 99%
“…7,8 For example, research indicates medically underrepresented minority physicians are important for delivery of primary care, provide care to indigent and minority populations, and improve access to health care services in underserved communities. 9,10,11,12 …”
mentioning
confidence: 99%